Consumption practices of women in the JN Surabaya taklim council - Srinarwati, Dwi Retnani (Jurnal Studi Komunikasi, 2022)
Currently, in Indonesia, many religious institutions serve as a forum for women's empowerment, service, and advancement, in the form of educational institutions, Islamic boarding schools, Taklim Council, socio-religious organisations, and women's NGOs. All of them have a concern for improving women's standard of living. Therefore, the recitation is a religious institution deeply rooted in Islamic society, one of which is the JN Surabaya Taklim Council. This study aims to determine women's consumption practices in the JN Surabaya Taklim Council. The type of research chosen in this study is qualitative research with a form of qualitative descriptive research. In this study, the JN Surabaya recitation council members were research informants. The conclusion of this study shows that women's consumption practices in the Salafi Taklim Council are studied as objects or behaviours that appear, as values, and meanings, until they are continued as 'signs'. Consuming signs as a hyperreality and hyperreality occurs through a process preceded by simulacra, which becomes the simulation process's vehicle.